The processing chain of the wide bandgap semiconductor SiC – How small steps enabled a mature technology - Wellmann, Peter; Steiner, Johannes; Strüber, Sven; Arzig, Matthias; Salamon, Michael; Uhlmann, Norman; Nguyen, Binh Duong; Sandfeld, Stefan (Diamond and Related Materials, 2023)
This work paper was presented as a keynote lecture at the international conference on diamond and related materials in Lisbon (Portugal) in the year 2022. This paper summarizes in the first part the processing chain of the semiconductor material SiC from the raw material to epitaxially-ready wafers as they are used for electronic device manufacturing. In the second part a current research study, the reduction of the basal plane dislocation density in SiC crystal growth is presented. Among other defects, basal plane dislocations belong to the more severe structural defects in SiC with respect to degradation during electronic device operation. In the third part the applicability of X-ray topography to reveal dislocations and other structural defects in SiC is outlined in a review style.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Bulk crystal growth; Dislocations; Processing chain; Silicon carbide